Integrasi Green Economy dan Blue Economy untuk Pembangunan Berkelanjutan - Khoirun Rizky; Misagi Mukhti Ginting; Rahmat Ibrahim Dalimunthe; Rizki Yawan Wijaya (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This essay focuses on sustainable development in archipelagic nations like Indonesia and how the Green and Blue economies may work together. This study identifies and analyzes a range of ideas, policies, and practices that bring the two economies together using a qualitative methodology and a literature review technique. A Green Economy is one that prioritizes social inclusion, resource efficiency, and low-carbon development. In the meantime, there's the Blue Economy, which promotes coastal environment preservation and economic growth via responsible resource management. According to this article's literature review, today's social and environmental problems may have their answers in the merging of these two economies. Sustainable development goals (SDGs) may be achieved, human well-being can be enhanced, and Indonesia's natural resource potential can be fully used by integrating sustainability concepts from both economies. This study's findings highlight the critical need of coordinating Green Economy and Blue Economy initiatives in order to foster mutually beneficial synergies that promote ecologically conscious and socially equitable sustainable growth.